Creep and recovery behavior of kenaf/polypropylene nonwoven composites. Issue 17 (2nd April 2014) - Hao, Ayou; Chen, Yizhuo; Chen, Jonathan Y.
ABSTRACT This article reports an exploratory study on the creep and recovery behavior of kenaf/polypropylene nonwoven composites (KPNCs), serving as a bio‐based substitution for polypropylene (PP) plastics in the automotive industry due to the environmental concern. The creep and recovery behavior of KPNC and solid virgin PP were performed by dynamic mechanical analyzer (DMA) which allowed it to be studied extensively. The linear viscoelastic limit (LVL) was found at 1 MPa. Two popular creep models, the four‐element Burgers (FEB) model and the Findley power law (FPL) model, were used to model the creep behavior in this study. The FEB model was found only appropriate for characterizing short‐term creep behavior. In contrast, the FPL model was satisfactory for predicting the long‐term creep performance. The long‐term creep behavior of KPNC in comparison to virgin PP plastic was predicted using the time‐temperature superposition (TTS) principle. The 1‐year creep strains were estimated to be 0.32% for KPNC and 1.00% for virgin PP at 40°C. A three‐day creep test was conducted to validate the effectiveness of the TTS prediction. KPNC showed a better creep resistance and higher recoverability than the virgin PP, especially in a high‐temperature environment. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40726.